(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2026)
This study evaluated the potential of vetiver grass biochar and liquid pineapple waste as organic nutrient sources in the hydroponic cultivation of Pak choy (Brassica rapa subsp. chinensis L). Six treatments were tested: a synthetic AB fertilizer control (T1), and five organic alternatives, including 100% pineapple waste (T2), 100% biochar (T3), and various combinations of both (T4–T6). Growth parameters such as chlorophyll content, plant height, number of leaves per plant, and biomass were measured. The control (T1) consistently exhibited superior performance, with the highest chlorophyll content (40.87 ± 7.02), plant height (13.85 ± 1.57 cm), and yield (42.44 ± 6.05 g). Among the organic treatments, T5 (75% biochar + 25% pineapple waste) produced the best results, with elevated chlorophyll content (25.10 ± 2.19) and the highest yield (3.84 ± 0.47 g), indicating the effect of the nutrient-retentive properties of biochar combined with the nutrient-rich composition of pineapple waste. Pearson correlation analysis revealed strong positive relationships among all parameters, with yield highly correlated with the number of leaves per plant (r = 0.99), plant height (r = 0.99), and chlorophyll content (r = 0.94). These results highlight the relevance of vegetative traits as reliable indicators of crop productivity in hydroponic systems. While entirely replacing synthetic nutrients remains challenging, the T5 formulation presents a potential alternative for reducing chemical inputs. This study supports the advancement of sustainable nutrient management practices in soilless agriculture. Furthermore, although vetiver grass biochar combined with liquid pineapple waste shows promise, further research is needed to understand the long-term effects on optimizing organic nutrient sources ratios, pH buffering, comprehensive nutrient uptake, and the synergistic potential with other organic nutrient sources or fertilizer practices. Such understanding is crucial for guiding future research in sustainable farming practices.